Influence of clinical and demographic variables on quality of life in patients with Parkinson's disease - Kenneth H. Karlsen; Jan Larsen; Elise Tandberg; J. G Maland (1999)
OBJECTIVES To identify the clinical and demographic factors that are associated with a poor quality of life in patients with Parkinson's disease. METHODS 233 of a total of 245 patients identified in a community based study in a Norwegian county participated in the study. Quality of life was measured by the Nottingham Health Profile (NHP). The results were compared with those in 100 healthy elderly people. Clinical and demographic variables were determined during a semistructured interview and by clinical examination by a neurologist. Multiple regression analyses were used to determine which variables were associated with higher distress scores. RESULTS Patients with Parkinson's disease had higher distress scores than the healthy elderly people for all the NHP dimensions. The variables that most strongly predicted a high total NHP score were depressive symptoms, self reported insomnia, and a low degree of independence, measured by the Schwab and England scale. Severity of parkinsonism contributed, but to a lesser extent. Nearly half the patients with Parkinson's disease reported lack of energy, compared with a fifth of the control group. Severity of depressive symptoms and a higher score on the UPDRS motor subscale only partly accounted for this finding. Only 30% of the variation in NHP energy score was explained by the predictive variables identified in this study. CONCLUSIONS Parkinson's disease has a substantial impact on health related quality of life. Depressive symptoms and sleep disorders correlated strongly with high distress scores. Patients with Parkinson's disease should be examined for both conditions, which require treatment. Low energy was commonly reported and may be a separate entity of Parkinson's disease.